CONTEMPORARY CONCEPTUALIZATIONS OF RUSSIAN CONSCIOUSNESS: UNDERSTANDING THE PHENOMENON OF NECRO-IMPERIALISM - Karpitsky, Mykolai (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
The article is devoted to the analysis of concepts and theoretical models that make it possible to explain the specific features of the contemporary Russian political regime and the transformation of imperial consciousness in the conditions of post-Soviet reality. The relevance of the study is determined by the need for a conceptual understanding of new forms of imperialism that cannot be fully described using the traditional categories of classical imperialism or ideologically driven totalitarianism. The objective of the study is to identify the semantic content of concepts and notions describing a new form of imperialism, to determine its socio-historical, worldview, existential, and socio-political foundations, and to compare this concept with other analytical approaches used in contemporary academic literature to describe the evolution of the Russian regime. The aim of the article is to determine in what way the contemporary Russian regime represents a new phenomenon compared with similar aggressive regimes that existed earlier in history. Research methodology includes methods of description, comparison, generalization, and critical evaluation of various conceptualizations of Russian imperialism in terms of their correspondence to historical realities and the current social situation. Research results. The article argues that despite ideological amorphousness and the desire to keep the population in a politically passive state, the Russian leadership has been able to mobilize society for an aggressive war by appealing to pre-reflective attitudes within mass consciousness. As a result, a particular public mindset has emerged – social necrophilia – signifying the mutation of imperial consciousness into a new form: necro-imperialism. In the Discussion, the main theoretical approaches used to analyze the contemporary Russian regime are compared. Conclusions state that necro-imperialism represents a specific form of imperial consciousness based on the cultivation of death, dehumanization, and the simplification of complex social reality